Enhancement of agricultural residue ash reactivity in concrete through the use of biofuel pretreatments - Ataie, Feraidon Farahmand (Kansas State University, 2013)
The cement industry is an important component in the quest to reduce global greenhouse gas emissions because of vast amounts of cement used annually. Incorporating supplementary cementitious materials (SCMs) into concrete is one alternative to reduce cement production and thereby reduce greenhouse gas emissions. This study investigated three types of agricultural residues, namely corn stover, wheat straw, and rice straw, in addition to bioethanol byproducts as potential resources for SCM production for concrete applications. Pretreatments, commonly used in bioethanol production, were used to improve pozzolanic reactivity of corn stover ash (CSA), wheat straw ash (WSA), and rice straw ash (RSA) in cementitious systems. In the first part of this research, the impact of distilled water and dilute hydrochloric acid pretreatments on pozzolanic reactivity of WSA, RSA, and CSA were studied. Results showed that pretreatments, particularly dilute acid, improved pozzolanic properties of CSA, WSA, and RSA by removing potassium and phosphorous from the biomass prior to ashing. In addition, WSA and RSA were shown to have similar pozzolanic reactivity to that of silica fume. In the second part of this study, suitability of high lignin residue (HLR), a bioethanol byproduct, for SCM production was investigated. It was shown that burning high lignin residue produces HLR ash that is very reactive in cementitious materials and can be used as a reactive SCM in concrete. The impact of each step in the production of bioethanol on the quality of bioethanol byproduct for subsequent burning and use in concrete was also studied. Sodium hydroxide and sulfuric acid pretreatments and enzymatic hydrolysis were used. Results revealed that sodium hydroxide pretreatment of the biomass have negative impact on biomass ash properties for concrete use because sodium hydroxide pretreatment did not remove phosphorous and other crystalline phases out of the biomass. However, sulfuric acid pretreatment of biomass greatly improved ash properties. It was also shown that enzymatic hydrolysis could have beneficial impact on ash properties because, during enzymatic hydrolysis, some phosphorous was leached out of the biomass.
Keywords: Pozzolanic materials; Biofuel pretreatments; Bioethanol by products; Agricultural residues; Civil Engineering (0543)